Performance evaluation of the Lien Son Irrigation System, North Vietnam : Master of Engineering Thesis - Nguyen, Van Tinh (School of Civil Engineering Bangkok, Thailand, 2020)
Irrigation performance indicators, which comprise engineering and economic indicators, allow an assessment on performance of irrigation systems. Indicators can be use to compare the system to other systems. Within the system, they can compared from year to year to indicate relative performance or trend. The Lien Son irrigation system located within the Red River Delta of Vietnam is chosen as study area. Based on available data of the study area, performance indicators will be determined, analysed and compared. Then some recommendations can be provided to improve irrigation performance for the study area.